Saphenous Vein-Sparing Strategies in Chronic Venous Disease (Springer International Publishing, 2018)
This book is designed to equip the reader with a detailed knowledge of the pathophysiology of chronic venous disease and an understanding of the clinical benefits of restoring venous drainage by saphenous vein-sparing procedures, including minimization of invasiveness and reduction of the recurrence rate. All of the techniques currently available for vein-sparing strategies, including novel endovenous options, are clearly described and illustrated, with explanation of the role and value of recent technical innovations. The reader is guided through the entire management process, starting from diagnosis and proceeding through evaluation of the individual patient's needs to the successful implementation of appropriate treatment. In addition, the literature on relevant diagnostic and therapeutic protocols is thoroughly reviewed, covering all significant publications to the present day. The content is kept as simple as possible to help those new to the field. At the same time, the deep insights into theoretical and technical aspects will support even the most advanced specialists in their everyday practice. .